(untitled) - Tacitus, Cornelius (New York, 1942)
After reading quite a few of the Loeb series historical books, Tacitus is refreshingly honest history. It has really detailed information for those interested in 1st century Roman history. A lot more detail than I have seen in any other source
Keywords: Nước Ý,Rome; Lịch sử,History